Spectroscopic Data of Steroid Glycosides Volume 4 - Ahmad, Viqar Uddin.; Ahmad, Viqar Uddin.; Basha, Anwer.; Basha, Anwer. (Springer US : Imprint: Springer, 2006)
Spectroscopic Data of Steroid Glycosides Dr. Viqar Uddin Ahmad, HEJ Research Institute of Chemistry, University of Karachi, Karachi, Pakistan Dr. Anwer Basha, Abbott Laboratories , Abbott Park, Illinois, USA Spectroscopic Data of Steroid Glycosides serves as an essential reference guide containing spectroscopic, physical and biological activity data of over 3500 steroid glycosides, offering the structures and the data of the naturally occurring glycosides of steroids. All compounds are arranged according to the structure of the aglycone, and, in its own class, according to the increasing molecular weight, making Spectroscopic Data of Steroid Glycosides extremely useful for the structure elucidation of new natural products, particularly glycosides. Spectroscopic Data of Steroid Glycosides offers a practical desk reference for all scientists and students interested in steroid glycosides and their biological and medicinal importance. The following data of the steroid glycosides, as available in published literature, are included: Name of the compound Chemical name of compound and its structure Source, name of the genus, species, authors, family of the biological source from which the glycoside has been isolated. Melting point Specific rotation Molecule weight Molecular formula UV spectral data : maxima, e or log e , solvent IR peaks in cm-1 with medium in which the spectrum was taken e.g. KBr, nujol, etc Proton magnetic resonance (PMR) chemical shifts, multiplicity of the peaks, coupling constants with assignments 13C-NMR (CMR) chemical shifts with assignments Mass spectral data with the technique used (e.g. Electron Impact (E.I.), Fast Atom Bombardment (FAB), positive ion or negative ion mode or any other technique CD or ORD data Biological Activity Full reference from which data have been taken.